Interview with His Holiness, The Ecumenical Patiarch Bartholomew 1: Carried out by Jean Catsiapis on behalf of Études helléniques/Hellenic Studies. - Ecumenical Patriarch, Bartholomew I; Catsiapis, Jean (Études helléniques / Hellenic Studies, 2001)
–